2009
DOI: 10.1111/j.1365-2494.2009.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of semi‐natural grassland through integrated generation of solid fuel and biogas from biomass. I. Effects of hydrothermal conditioning and mechanical dehydration on mass flows of organic and mineral plant compounds, and nutrient balances

Abstract: The use of semi-natural grasslands for the production of renewable energy through conventional conversion techniques faces major limitations because of chemical and physical properties of the biomass. A new conversion procedure was developed which separates the biomass, as silage, into a liquid phase for biogas production and into a solid fraction to be used as fuel. Separation (mechanical dehydration) is carried out with a screw press after mashing with water (hydrothermal conditioning). The effect of hydroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 10 publications
7
79
1
Order By: Relevance
“…Compared to other research results from semi-natural grassland biomass [9,10,18,19], the mineral concentration values for the L0 biomass are within the expected range for biomass harvested in June; however, the values for the L100 samples for Ca, Mg and N were considerably higher. This corresponds with previous findings, which likewise found higher mineral content, particularly for Ca, Mg and N [20,21], in legumes and other dicotyledonous plants compared to grasses.…”
Section: Chemical Composition Of Silage and Press Cakecontrasting
confidence: 55%
See 2 more Smart Citations
“…Compared to other research results from semi-natural grassland biomass [9,10,18,19], the mineral concentration values for the L0 biomass are within the expected range for biomass harvested in June; however, the values for the L100 samples for Ca, Mg and N were considerably higher. This corresponds with previous findings, which likewise found higher mineral content, particularly for Ca, Mg and N [20,21], in legumes and other dicotyledonous plants compared to grasses.…”
Section: Chemical Composition Of Silage and Press Cakecontrasting
confidence: 55%
“…Wachendorf et al [9] observed methane yields with a mean value of 218 L N ·CH 4 ·kg −1 VS for five semi-natural grassland areas, and Piepenschneider et al [25] measured values of 222 L N ·CH 4 ·kg −1 VS for urban road-side cut material from the city of Kassel, Germany. While these values were slightly lower than the values reported in this study, higher methane yields (285-388 L N ·CH 4 ·kg −1 VS) have also been reported by Richter et al [26] for samples from an alluvial meadow with successive harvesting dates, with the tendency of decreasing methane yields with progressing sward maturity.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some instances, a positive environmental effect may be achieved by using the vegetation already growing on the land for bioenergy rather than using the land for the cultivation of energy crops. Wachendorf et al (2009) showed that semi-natural grassland in Europe can be used for bioenergy production by separating the silage harvested into a liquid fraction for biogas production and a solid fraction for combustion. Similarly, baler technology now exists for harvesting biomass from brushlands.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…lactic acid, amino acids). Wachendorf et al (2009) reported that fractionation reduces herbage water content and the concentration of minerals, and leads to the enrichment of fibrous constituents in the press-cake fraction. Similarly, reported that > 0.55 of the N and ash was removed from the press-cake fraction relative to the fresh material pre-ensiling.…”
Section: Fractionationmentioning
confidence: 99%